Synthesis and crystal structures of 1-benzoyl-4-(4-nitrophenyl)piperazine and 1-(4-bromobenzoyl)-4-phenylpiperazine at 90 K - Sreeramapura D. Archana; Haruvegowda Kiran Kumar; Holehundi J. Shankara Prasad; Hemmige S. Yathirajan; Sean Parkin (Acta Crystallographica Section E: Crystallographic Communications, 2022)
Synthesis and crystal structures of 1-benzoyl-4-(4-nitrophenyl)piperazine, C17H17N3O3, (I) and 1-(4-bromobenzoyl)-4-phenylpiperazine, C17H17BrN2O, (II) are described. Compounds I and II crystallize in the orthorhombic and monoclinic crystal systems with space groups Pna21 (Z′ = 2, I) and P21 (Z′ = 1, II), respectively. The crystal of II was a two-component aggregate, treated as a `twin' for data-acquisition purposes. There are no conventional hydrogen bonds in either I or II, but there are weaker C—H...O contacts. Each molecule consists of a central piperazine ring in a chair conformation, with either benzoyl and nitrophenyl (I) or 4-bromobenzoyl and phenyl (II) groups attached to different nitrogen atoms of the piperazine. The various atom–atom contact coverages as quantified by Hirshfeld surface analysis fingerprint plots are given.